NEW METOD OF BONE TISSUE DEFECT RECONSTRUCTION IN LONG BONE’S METAEPIPHYSIS FOR THE SURGICAL TREATMENT OF BENIGNE SKELETAL TUMOURS - G. P. Kotelnikov; A. Yu. Terskov (Креативная хирургия и онкология)
In the  article  we  describe  the  new  method for  bone  tissue  defect grafting in the metaepiphiseal zone  of   long bones  with allogenous grafts fixed in the  form  of the  letter “T”. Application of the method provides the congruency retention to prevent the deformity of articular surface during surgical treatment of the patients with benign  bone tumors.